The first point will be (0,0), then (1,4), then (2,8)
Answer: - 48 (edit: omg i didnt see the minus)
Step-by-step explanation: i mean, only z multiply x
z = 12
x = 4
zx
= z multiply x
= 12 x - 4
= - 48
^_____^
Answer:
I'm guessing C
Step-by-step explanation:
I don't think this is the correct way to answer it. But I litterly rotated it in my brain and got 7.5....
The simplified expression for 6(2( y + x)) is 12y + 12x.
Accordin to the given question.
We have an expression
6(2( y + x))
Therefore,
The simplified expression for 6(2( y + x)) is given by
6(2(y + x))
= 6(2y + 2x) (by distributive law)
= 12y + 12x (by distributive law)
Hence, the simplified expression for 6(2( y + x)) is 12y + 12x.
Find out more information about simplified expression here:
brainly.com/question/18077352
#SPJ4
Answer: 2.25 = 18.90
Step-by-step explanation: Hope This Helps